2021
DOI: 10.1186/s12887-021-03028-w
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ pandemic NICU experience in the United States: a qualitative study

Abstract: Background Prior to the COVID-19 pandemic, parents of infants in the Neonatal Intensive Care Unit (NICU) frequently reported high levels of stress, uncertainty, and decreased parenting confidence. Early research has demonstrated that parents have had less access to their infants in the hospital due to restrictions on parental presence secondary to the pandemic. It is unknown how parents have perceived their experiences in the NICU since the beginning of the COVID-19 pandemic. The purpose of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
32
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 50 publications
9
32
0
1
Order By: Relevance
“…This lack of family involvement affected not only the medical staff but also had a direct impact on the family as well. These feelings were shared by parents of infants in the NICU in both the Netherlands (Meesters et al, 2021 ) and in the United States (Vance et al, 2021 ). Both these studies found that the parents were upset with the decision that the healthcare systems made and that parents needed to be consulted as part of this process.…”
Section: Findings and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This lack of family involvement affected not only the medical staff but also had a direct impact on the family as well. These feelings were shared by parents of infants in the NICU in both the Netherlands (Meesters et al, 2021 ) and in the United States (Vance et al, 2021 ). Both these studies found that the parents were upset with the decision that the healthcare systems made and that parents needed to be consulted as part of this process.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Both these studies found that the parents were upset with the decision that the healthcare systems made and that parents needed to be consulted as part of this process. Based on the findings from the study by Meesters et al (2020) and Vance et al ( 2021 ), a more family-centred approach is required when making important decisions that affect the care of vulnerable infants and their families.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Os pais vivenciaram momentos de estresse (Mengesha et al, 2022, Erdei et al, 2022, Meesters et al, 2021, problemas emocionais (Holly et al, 2021, Garfield et al, 2021, Bembich et al, 2020, Vance et al, 2021, Mengesha et al, 2022, Adama et al, 2022, Polloni et al, 2021, impactos na amamentação (Garfield et al, 2021, Muniraman et al, 2020 limitação do apoio social após a alta (Galeano et al, 2021), dificuldade de interação com profissionais de saúde (Mengesha et al, 2022), dificuldades de cuidados com o bebê (Adama et al, 2022, Muniraman et al, 2020, Reichert et al, 2022, Polloni et al, 2021, dificuldade em ter contato físico com o bebê (Polloni et al, 2021, Adama et al, 2022 e a interrupção temporária da segunda etapa do Método Canguru (MC) (Reichert 2022). Todos esses preditores prejudicaram o CCF, mas que devem proporcionar uma reflexão acerca da interação e intervenção da família na prática clínica, pois a partir dessas reflexões e princípios, pode-se estabelecer a competência parenteral, bem como, contribuir para que pais e profissionais trabalhem em parceria na unidade neonatal (Corrêa et al, 2015).…”
Section: Discussionunclassified
“…Hospitalization, such as having an infant in the neonatal intensive care unit (NICU), can become a stressful life event and a source of trauma for some [ 10 , 11 ]. Postpartum women who have an infant in NICU care may experience an increased risk of developing MH conditions [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. However, studies exploring the association of NICU hospitalizations and maternal MH have not used large national samples.…”
Section: Introductionmentioning
confidence: 99%
“…Limited literature evaluates the relationship between NICU hospitalization and symptoms of depression and anxiety among postpartum women. In addition, the existing literature uses cross-sectional designs [ 12 , 13 , 14 , 17 , 18 ], small sample sizes [ 12 , 13 , 14 , 17 , 18 , 19 ], a focus on a single region [ 12 , 13 , 14 , 15 , 16 , 17 , 18 ], and qualitative methodologies [ 15 ]. Additionally, it does not typically control for antenatal MH conditions [ 10 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%